Pemetaan Penyakit Tuberculosis Dengan Sistem Informasi Geografis Di Wilayah Bantul - Andhy Sulistyo (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis which is still a major health problem, both in the world and in Indonesia. Based on health data, the number of tuberculosis cases in the Bantul region in 2018 was 406 cases, in 2019, there was an increase of 1,003 cases, a decrease in 2020 by 708 and in 2021 678 cases. The purpose of this study was to determine the mapping of the distribution of tuberculosis cases in Bantul Regency and high sub-districts in 2021 and graph the number of cases based on gender and age, environmental factors that influence (temperature, humidity, rainfall, population density). The type of research used in this scientific paper uses qualitative research with a case study design. The results of the research mapping the distribution of the highest tuberculosis cases in Bantul District as many as 383 cases and in Banguntapan Village Area as many as 40 cases. Tuberculosis cases based on sex were more male as many as 401 cases. For cases based on the age group 0-4 years, the highest cases were 170 cases. The factors causing the high incidence of tuberculosis are rainfall, temperature, humidity and population density factors. Districts with high cases related to environmental factors are in Banguntapan, Bantul and Pandak Districts. The process of collecting health data has been computerized, with the highest distribution of cases in Bantul Regency and the highest in Banguntapan Village. Tuberculosis cases are more male than female. Environmental factors related to rainfall and population density.